Continuous Control Set Model Predictive Control of a Modular Multilevel Hexverter - Uriarte-Gonzalez, M (Institute of Electrical and Electronics Engineers Inc., 2023)
Fractional frequency transmission systems are capable of transmitting power through longer distances when compared with currently used transmission systems. However, research on the power electronics topologies required to transform the frequency of the system is still being carried out. In this paper, a control strategy based on model predictive control is proposed to regulate the cluster capacitor voltages of an AC-AC converter topology denominated as hexverter. The feasibility of the proposed control strategy is demonstrated using simulation results of a hexverter connected to two AC systems with different frequencies. © 2023 IEEE.